Patient-Reported Experiences in Voxelotor-Treated Children and Adults with Sickle Cell Disease: A Semistructured Interview Study. (28th January 2023) - Brown, Clark; Idowu, Modupe; Drachtman, Richard; Beaubrun, Anne; Agodoa, Irene; Nguyen, Andy; Lipman, Kelly; Moshkovich, Olga; Murphy, Ryan; Bellenger, M. Alex; Smith, Wally
Abstract : Objective . Voxelotor is a first-in-class sickle hemoglobin–polymerization inhibitor that was approved in 2019 by the US Food and Drug Administration for treatment of patients with sickle cell disease (SCD) aged ≥12 years; in 2021, the approval was extended to children with SCD aged 4 to 11 years. Additionally, both the Ministry of Health and Prevention for the United Arab Emirates and the European Commission granted marketing authorization for voxelotor in September 2021 and February 2022, respectively, for treatment of SCD in adults and pediatric patients aged ≥12 years. Thus, additional information on the patient experience with voxelotor would be useful for patients, caregivers, and healthcare professionals alike. The purpose of this study was to conduct semistructured interviews in an effort to understand the experiences and perspectives of voxelotor-treated patients with SCD. Methods . One-time semistructured interviews with adults, adolescents, and children with SCD and their primary caregivers were conducted in the United States. Twenty-three adults and adolescents were recruited across 4 clinical sites, and 10 children-caregiver dyads were recruited from a single site. The interview was designed to elicit patient perspectives on symptomatic changes with voxelotor and the impact of treatment on patients' perceived health-related quality of life. Individual interview transcripts were analyzed using a thematic analytic approach, and concept saturation was assessed in both cohorts. Results . Most patients reported improvements in their SCD symptoms with voxelotor treatment, specifically regarding pain crises, jaundice, and fatigue. Almost all patients experienced improvements in self-reported health-related quality of life with voxelotor treatment. Conclusions . This study provides patient and caregiver perspectives on the symptomatic benefits of voxelotor treatment. These findings not only highlight the benefits of voxelotor treatment in improving symptoms and increasing health-related quality of life across the entire SCD population but also can inform further research on SCD-specific patient-reported outcomes.